2016
DOI: 10.3389/fncom.2016.00118
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Nociceptive Information Encoded in the Temporal Discharge Patterns of Cutaneous C-Fibers

Abstract: The generation of pain signals from primary afferent neurons is explained by a labeled-line code. However, this notion cannot apply in a simple way to cutaneous C-fibers, which carry signals from a variety of receptors that respond to various stimuli including agonist chemicals. To represent the discharge patterns of C-fibers according to different agonist chemicals, we have developed a quantitative approach using three consecutive spikes. By using this method, the generation of pain in response to chemical st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…However, is important to note that pain intensity is not simply encoded by frequency, and that spike timing and temporal pattern are also of crucial importance (Cho et al . 2016; Barkai et al . 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, is important to note that pain intensity is not simply encoded by frequency, and that spike timing and temporal pattern are also of crucial importance (Cho et al . 2016; Barkai et al . 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A redistribution of HCN channels after nerve damage would have a decisive influence on these spike trains. It has long been suggested that both the magnitude and the quality of pain sensation are encoded by the temporal summation of the nociceptive discharge (Koltzenburg and Handwerker, ; Cho et al., ) and that different responses before and after a nerve injury might be associated with the temporal patterns of spontaneous spikes (Sandkühler, ). However, the relevance of the temporal patterns of ectopic discharges in the nociceptive message has never been examined in depth before.…”
Section: Introductionmentioning
confidence: 99%
“…This change in peak instantaneous frequency may be too narrow to encode and convey the changes in response to stimuli. We, therefore, hypothesized that in addition to the spike rate coding (Adrian and Zotterman, 1926), the nociceptive neurons might also use "temporal" coding to integrate and encode the information about different response properties via different timing patterns of spikes (Cho et al, 2016). Accordingly, we analyzed the spiking activity over time following a capsaicin-current stimulation of all terminals in the "realistic" terminal tree in normal conditions, in inflammatory hyperalgesia conditions, in which the SIZ was shifted toward the terminals and in neuropathic pain conditions, in which sub-and suprathreshold current noise was injected (Figure 11D).…”
Section: Resultsmentioning
confidence: 99%
“…We show that in modeled pathological conditions in which nociceptive neurons become hyperexcitable, the changes in their gain are encoded by the differences in the spike arrival time. The differences in spike patterns between capsaicin and GABA-evoked responses were recently correlated with the differences in the resulting pain sensation following either capsaicin or GABA stimulation (Cho et al, 2016). Thus, the difference in the timing pattern of spikes could convey important information regarding the gain of the inputoutput properties of the nociceptive neurons.…”
Section: Resultsmentioning
confidence: 99%